Nondestructive Method for Ripening Prediction of Papaya. (2015) - Bhosale, A.A.; Sundaram, K.K.
Abstract: It is critical to investigate some physical and mechanical properties of papaya fruits at different level of ripeness. Ripening of climacteric fruit such as papaya fruit depends on the ethylene action which later accompanied by softening process that can influence postharvest quality and storability of the fruit. Relation between various stages of ripeness is going to be determined. Ripening is a process in fruits that causes them to become more palatable. In general, a fruit becomes sweeter, less green, and softer as it ripens. Even though the acidity of fruit increases as it ripens. All physical and mechanical properties of papaya fruit except deformation had high correlation with stage of ripeness. The firmness, rupture energy and hardness decrease as papaya fruit ripened. To find out ripeness of papaya, use capacitive sensing system, color index method and eco measurement is utilized. Firmness shows a correlation up to 99% to capacitance method.